Perbedaan Kadar Brain Derived Neurotropic Factor Neonatus Dari Ibu Hamil Normal Dan Anemia Defisiensi Besi - Mardiah, Ainal; Amir, Arni; Friadi, Andi; Nasrul, Ellyza (Jurnal Endurance, 2018)
Iron deficiency anemia is anemia caused by iron deficiency in the blood. Maternal iron deficiency affects the low iron reserves in neonates and it also influences on Brain Derived Neurotropic Factor (BDNF)  which affects cognitive function. The purpose of this study was to determine the difference mean of BDNF in neonates from normal pregnant women and pregnant women with iron deficiency. The design of this research was Cross Sectional design. This research was conducted in Community Health Center of Lubuk  Buaya, Ambacang Community Health Center, Community Health Center of Ikur Koto Health Center and Biomedical Laboratory of Andalas University on February 2017 to April 2018. There were 42 pregnant women was selected as sample e of this research. The samples were chosen by Consecutive Sampling. Then, the sample is divided into two groups: normal pregnant women and pregnant women with iron deficiency anemia. BDNF are examined by the ELISA. Next, the data were analyzed by using T test. The levels of BDNF neonates in normal pregnant group was 3.65(ng/ml) and the anemia pregnant group was 1.74(ng/ml) (p <0.05). There was significant difference of BDNF levels in neonates from normal pregnant women and pregnant women with iron deficiency anemia. The conclusion of this study is there is a difference of average BDNF in neonates from normal pregnant women and pregnant women with iron deficiency. Anemia defisiensi besi adalah anemia yang disebabkan karena kekurangan zat besi dalam darah. Defisiensi besi  maternal berdampak pada rendahnya cadangan besi pada neonatus dan berdampak terhadap ekspresi Brain Derived Neurotropic Factor (BDNF) yang berpengaruh pada fungsi kognitif. Tujuan penelitian ini adalah untuk mengetahui perbedaan rerata kadar BDNF pada neonatus dari ibu hamil normal dan ibu hamil defisiensi besi. Desain penelitian ini adalah Cross Sectional. Penelitian dilakukan di Puskesmas Lubuk Buaya, Puskesmas Ambacang, Puskesmas Ikur Koto dan Laboratorium Biomedik Universitas Andalas pada bulan Februari 2017 – Juli 2018. Sampel Penelitian adalah ibu hamil sebanyak 42 orang yang dipilih secara Consecutive Sampling, sampel dibagi menjadi dua kelompok yaitu ibu hamil normal dan ibu hamil anemia defisiensi besi. BDNF diperiksa dengan metode ELISA. Data dianalisa menggunakan uji T test. Kadar BDNF neonatus pada ibu kelompok normal adalah 3,65(ng/ml) dan kelompok ibu anemia adalah 1,74(ng/ml) (p<0,05). Terdapat perbedaan bermakna kadar BDNF pada neonatus dari ibu hamil normal dan ibu anemia defisiensi besi.